Innovative Syariah Financial Index: A New Metric for Evaluating Financial Performance - Edriani, Devi Edriani; Novita , Wellia (Al Urwah : Sharia Economics Journal, 2025)
This research examines the relationship between the Innovative Syariah Financial Index and financial performance at Bank Syariah Indonesia KC Jakarta Pemuda, focusing on the roles of financial innovation, marketing strategies, risk management, and Sharia compliance. Utilizing a quantitative approach, data was collected from 45 employees through structured questionnaires, and analysis was conducted using SmartPLS to evaluate the proposed relationships. The findings reveal that financial innovation significantly impacts financial performance, with marketing strategies acting as a critical facilitator of this relationship. Additionally, the study highlights the significant role of Sharia compliance in shaping effective risk management practices, which in turn positively influence financial performance. These results underscore the importance of integrating ethical considerations into risk management and aligning marketing efforts with innovative product offerings to achieve sustainable growth in the Islamic banking sector. The research contributes valuable insights into the dynamics of Islamic finance and offers practical implications for enhancing operational effectiveness while adhering to Sharia principles.